Clinical significance of baseline and post-treatment CXCR1 expression in breast cancer women received neoadjuvant chemotherapy - Sara Adel Amin; Emad Abd El Mongy Sadaka; Khalid Ahmed Ismail; Ashraf Fathy Barakat; Ahmed Abdel Aziem Menaisy; Amr Abd Elmoneim Mahmoud (Journal of the Pakistan Medical Association, 2023)
Objective: To examine the chemokine receptor type 1 expression in breast cancer tissues before and after neoadjuvant chemotherapy, and its relationship with pathological response to neoadjuvant chemotherapy and other clinical variables. Methods: The prospective study was conducted at Kafrelsheikh University Hospital, Egypt, from November 2018 to March 2021, and comprised female patients with new histopathologically proven breast cancer eligible for chemotherapy. Paraffin blocks of tumour specimens were stained immunohistochemically using concentrated rabbit anti-human chemokine receptor type 1 polyclonal antibody kits. The patients were followed up for treatment response, disease recurrence and mortality. Data was analysed using SPSS 25. Results: Of the 100 patients with mean age 50.2±12.1 years, 40(40%) in group A with mean age 55.1±9.3 showed marked response and 60(60%) in group B with mean age 47.0±12.7 years showed mild/moderate response (p<0.001). Group A patients had significantly lower baseline and post-treatment chemokine receptor type 1 expression compared to group B patients (p<0.05). The change in chemokine receptor type 1 expression was not significantly different (p>0.05). Patients with tumour grade 3 had significantly higher baseline chemokine receptor type 1 expression compared to patients with tumour grade 2. Tumour stage and post-treatment chemokine receptor type 1 expression were also significantly interlinked (p<0.05). Multivariate regression analysis identified patients’ age, baseline chemokine receptor type 1 and post-treatment chemokine receptor type 1 expressions as predictors of treatment response. Conclusions: There was found to be an association between baseline and post-treatment chemokine receptor type 1 expression in breast cancer tissues and pathological response to neoadjuvant chemo therapy in such patients. Keywords: Neoadjuvant therapy, Paraffin, Breast neoplasms, Receptors, Chemokine.